THE DEPICTION OF WOMEN VICTIMIZATION IN THE SELECTED NOVELS OF BAPSI SIDHWA - Chauhan, Shreemayee; Preeti Pankaj Gupta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study uses a feminist and post-colonial perspective to critically analyse how women are portrayed in Bapsi Sidhwa's writings. It explores the themes of Identity crisis, gender inequity, cultural limitations, and the fight for independence in patriarchal settings. By examining their experiences of marginalization, resiliency, and self-assertion, the study explores the difficulties faced by female protagonists navigating post-colonial environments. The study contrasts tradition and modernity while highlighting concerns of exploitation, feminine bonding, and cultural identity through Sidhwa's works such as Ice-Candy Man, The Pakistani Bride, and An American Brat. The study provides insights into the changing roles and status of women in South Asian literature and society by examining these narratives and shedding light on the specific and universal difficulties that women encounter. By offering a framework for comprehending women's struggles and empowerment in modern literature, this study advances feminist discourse.